Feed Me Sustainably – A tool for improving the sustainability of public food procurement programmes using threatened crop diversity - Drucker, Adam G.; Ramírez, Marleni; Cueto, J.; Watts, S.; McKeown, Peter C.; Spillane, Charles; Hunter, Danny (2022)
In order to facilitate sustainability transitions for food procurement programs, the Alliance of Bioversity-CIAT is developing a decision-support tool to evaluate and monitor the socio-economic and environmental impacts of different food procurement scenarios. Such a “Feed Me Sustainably” (FMS) tool can help build a more reliable evidence-base for policy-makers, food procurement managers, and other key stakeholders to address the challenges and opportunities for improving the sustainability and food security outcomes from school meal procurement programs. Here we report on the first steps towards the development of such a FMS tool with potential global applicability and its initial application in Peru.